Co/Mo2C multilayer as X‐ray mirror: Optical and thermal performances. Issue 4 (4th December 2013) - Yuan, Yanyan; Guen, Karine Le; André, Jean‐Michel; Wang, Zhanshan; Li, Haochuan; Zhu, Jingtao; Mény, Christian; Giglia, Angelo; Nannarone, Stefano; Jonnard, Philippe
Abstract We combined soft X‐ray reflectivity (SXR) and X‐ray standing‐wave‐enhanced fluorescence to study the optical performance and the thermally‐induced interface behavior of Co/Mo2C nanometric multilayers, designed to work in the soft X‐ray range close to the Co L3 absorption edge. Grazing X‐ray reflectivity measurements were performed at 0.154 nm (Cu Kα line) and at two wavelengths in the soft X‐ray range, 1.59 and 1.33 nm, close to and far from the Co L3 edge. In the fluorescence experiment the intensity of the Co Lα emission was measured by the standing‐wave method within a Co/Mo2C stack. We found that the Co/Mo2C multilayers present good optical performance in the soft X‐ray range up to 600 °C annealing temperature. Indeed, the reflectivity value in the soft X‐ray range at a grazing angle of 11° is 25% for the as‐deposited sample, then slightly varies with annealing and is still 20% after annealing at 600 °C. This demonstrates the good thermal stability of the Co/Mo2C multilayer. We used a simplified two‐layer model and modified optical indices of the Co nanofilms to fit the experimental X‐ray reflectivity curves. The same modified values of the optical indices are used to fit the X‐ray standing‐wave curves, confirming the usefulness of the model of the stack.